Classification of Color Pigments of Robusta Coffee Plants with Mordanting Method Applied to Cloth Masks - susi susyanti; Okta Amelia; Muhammad Hajid An Nur; PG. Wisnu Wijaya (Journal of Science and Applicative Technology, 2021)
Part of the coffee plant as a whole from the roots until the fruit can produce dye pigment, the coffee plant that is made sample is Robusta coffee plant (Coffee Robusta). The absence of natural color calcification uses one whole plant. So it is made from coffee plants typical of Lampung as a local identity. The mordanting process of the extract results in the parts of the coffee plant on the French cotton fabric, producing pigments that can be used as dyes for textiles. This method is easy to classify the pigment from the parts of the coffee plant. Classifications of colors obtained from warm, soft, and cold color ranges (casual, beautiful, Natural, beautiful, romantic, elegant, classic, clear and cool casual). This research was conducted to classify various colors of Robusta coffee plants, roots, wood, bark, ranting, wet leaves, dried leaves, wet skin, wet bark, dry hard skin, wet seeds, dried seeds, and grain powders with The mordanting process is transferred on the cloth. From the results of the experiment, excellent color absorption resulted from wet fruit skin with a tendency towards warm colors and applied to the mask as an example of the product by means of a brush so that not much wasted color content. way in brushes and applications on this mask is an effort to respond to environmental issues and new normal.